Bacterial Infection Disrupts the Intestinal Bacterial Community and Facilitates the Enrichment of Pathogenic Bacteria in the Intestines of Penaeus vannamei - Renjun Zhou; Shaoping Weng; Jianguo He (Microorganisms)
Pathogenic infections can reshape the intestinal microbiota of aquatic animals, thereby impacting their health status. In this study, we aimed to investigate whether Vibrio parahaemolyticus infection induces dysbiosis in the intestinal bacterial community of Penaeus vannamei and to assess the associated ecological risks. Our findings revealed the deterministic processes in intestinal bacterial community assembly during bacterial infections, indicating that host selection, i.e., host immune response post-infection, has a significant influence on intestinal microbes. More importantly, we found that bacterial infection reshaped the intestinal community by reducing the relative abundance of probiotic Ruegeria species (e.g., R. atlantica, R. lacuscaerulensis, R. conchae, R. profundi, R. arenilitoris, R. pomeroyi) and increasing the relative abundance of Vibrio species (V. harveyi, V. sinaloensis, V. coralliilyticus, and V. brasiliensis). Significant negative correlations were observed between the relative abundance of these Ruegeria species and the relative abundance of Vibrio species. Moreover, the control P. vannamei contained a substantially higher number of keystone species belonging to Ruegeria in the bacterial community network, whereas bacterial infection individuals had few or no keystone species belonging to Ruegeria, with keystone species belonging to Vibrio becoming more prominent. Thus, the significant increase in Vibrio species abundance in the P. vannamei intestine following bacterial infection was associated with the marked reduction in Ruegeria species. Our findings will provide valuable insights into the complex interactions among bacterial infection, intestinal microbiota, and host health, and they provide guidance for the development of probiotics in promoting the healthy culture of P. vannamei.